Interferon-directed inhibition of chronic murine leukemia virus production in cell cultures: lack of effect on intracellular viral markers. - Friedman, R M (1975)
Extracellular murine leukemia virus (MLV) reverse transcriptase activity was decreased by interferon treatment in four interferon-sensitive mouse cell lines which were chronic MLV producers. In three cell lines which were relatively insensitive to interferon, extracellular enzyme activity remained unchanged by interferon treatment. The concentrations of interferon used had no effect on DNA synthesis or cell replication of AKR,C+ cells which were chronic producers of AKR-MLV. In AKR,C+ cultures interferon treatment also had no effect on the level of intracellular viral reverse transcriptase activity in spite of an inhibition of extracellular enzyme activity. Treatment of AKRC+ cultures with interferon for 9 days inhibited extracellular viral reverse transcriptase levels throughout the period of treatment; however, the intracellular enzyme activity remained unchanged, and concentrations of viral p30 (gs) antigen were increased in the interferon-treated cells. When the cells were washed to remove interferon, however, virus production rapidly rose and intracellular p30 antigen fell to the levels of untreated AKR,C+ cells. These and previously reported results suggested that in interferon-treated AKR,C+ cells virus production is inhibited at a late step in the MLV replication cycle, either directly or through the inhibition of the production of a protein required for virus assembly.